The Impact of Environmental, Social, and Governance (ESG) Risk Rating on Audit Opinions: Empirical Study on IDX80-Listed Companies (2022–2023) - Hasna Nur Laila; Triani, Ni Nyoman Alit (Majapahit Journal of Islamic Finance and Management, 2025)
This study investigates the influence of Environmental, Social, and Governance (ESG) Risk Rating on the likelihood of receiving a modified audit opinion among companies listed on the IDX80 index for the period 2022–2023. Employing a quantitative associative research design, the study uses binary logistic regression to analyze 144 firm-year observations drawn from 72 companies that met the criteria of publishing complete financial and sustainability reports. The ESG Risk Rating was treated as the independent variable, while leverage and return on assets (ROA) were used as control variables. Audit opinion, classified as either unqualified or modified, served as the dependent variable. The findings reveal a significant positive relationship between ESG risk and modified audit opinions, suggesting that firms with higher ESG risk (i.e., weaker ESG performance) are more likely to receive modified opinions. Conversely, leverage, liquidity show positive and significant effect, cashflow and firm size show negative effect, meanwhile ROA, firm age, and sales growth did not show significant influence. The model exhibited strong predictive ability with a classification accuracy of 91,7% and a Nagelkerke R² of 74,8%. These results highlight the importance of ESG performance in audit assessments and suggest that auditors increasingly consider non-financial information. The study implies that improving ESG practices and disclosure can enhance a company’s credibility and reduce audit risks, offering valuable insights for stakeholders, regulators, and corporate decision-makers.